The Use of Psalm 68:19 in Ephesians 4:8 as an Intertextual Study - Gilbeth Pramana Saputra; Lilis Setyarini (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
The text of Psalm 68:19, quoted by Paul and used as a citation in Ephesus, is categorized by biblical scholars as a crux interpretetum, one of the verses that are difficult to interpret. There are two problems found in Paul's use of the quotation from Psalm 68:19 in his writing in Ephesians 4:8, making this a challenging verse to interpret. First, there is no apparent textual connection between Psalm 68:19 and Ephesians 4:3. Second, the motif and meaning of Paul's use of Psalm 68:19 as a reference in Ephesians 4:8 have not been clearly identified by the author. Among the eight biblical scholars, six different answers have been found, each differing from the others. The approach used to analyze the use of Psalm 68:19 in Ephesians is an intertextual approach, which is a method to find solutions to the three issues mentioned above. The result of this research is that Paul quotes Psalm 68:19 in Ephesians 4:8 as the foundation of his kerygma, asserting that his teaching in the context of Ephesians 4 is the same truth as the teaching in Psalm 68:19, which also harmonizes with the context of Numbers 8. The quotation of Psalm 68:19 in Ephesians 4:8 by Paul affirms that what he teaches is the same truth as the Old Testament. God and Jesus Christ are the same Person acting on His people, both giving and receiving among humanity.